Siren City : Sound and Source Music in Classic American Noir - Miklitsch, Robert, 1953- (UPCC book collections on Project Muse., 2011)
Despite the pervasive presence of musical numbers in classic film noir, not to mention the use of voice-over and hard-boiled dialogue, the genre like the medium in general, motion pictures has been viewed primarily in visual terms, whether it's high-contrast lighting or night-for-night shooting, oblique angles or claustrophobic framing, "dissonant" deep-focus compositions or the "archetypal noir shot": "the extreme high-angle long shot." While film noir has also been defined in terms of, among other things, its mood and motifs, plot and mode of narration, sociocultural significance and conditions of production, the emphasis on visual style, an emphasis that's especially pronounced in Paul Schrader's "Notes on Film Noir" ("the theme is hidden in the style"2), has resulted in a corresponding disregard of the sonic or acoustic register.